Ferroelectric to Relaxor Transition in BaTiO3–Bi(Zn2/3Nb1/3)O3 Ceramics. Issue 1 (11th October 2016) - Wu, Longwen; Wang, Xiaohui; Shen, Zhengbo; Li, Longtu
Abstract : The (1− x )BaTiO3 – x Bi(Zn2/3 Nb1/3 )O3 ( x = 0.01–0.30) ceramics were synthesized by solid‐state reactions. The solubility limit was determined to be x = 0.20. A systematic structural transition from a tetragonal phase ( x ≤ 0.034), to a mixture of tetragonal and rhombohedral phases (0.038 ≤ x ≤ 0.20), and finally to a pseudocubic phase ( x ≥ 0.22) at room temperature was identified. Dielectric measurement revealed a ferroelectric ( x ≤ 0.04) to relaxor ( x ≥ 0.06) transition with permittivity peak broadening and flattening, which was further verified by Raman spectroscopy and differential scanning calorimetry (DSC). Activation energies obtained from the Vogel–Fulcher model displayed an increasing trend from ~0.03 eV for x ~ 0.05, to unusually high values (>0.20 eV) for the compositions with x ≥ 0.15. With the increase in Bi(Zn2/3 Nb1/3 )O3 content, the polarization hysteresis demonstrated a tendency from high nonlinearity to sublinearity coupled with the reduction in remnant polarization and coervice field. The deconvolution of the irreversible/reversible polarization contribution was enabled by first‐order reversal curve distributions, which indicates that the decreasing polarization nonlinearity with the increase in Bi(Zn2/3 Nb1/3 )O3 concentration could be related with the change from the ferroelectric domain and domain wall contributions to the weakly coupled relaxor behaviors.